A review of comparison on efficacy, safety and cost effectiveness of cholinesterase inhibitors, NMDA antagonists and combination therapy in the treatment of Alzheimer’s disease - Haque, Mushfiqul (BRAC University, 2019)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.